2011
DOI: 10.5558/tfc2011-007
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of The Efficacy of Vegetation Management Alternatives for Conifer Regeneration in Boreal Forests

Abstract: In this paper, we discuss the broad array of treatments that could be used to control competitive vegetation in conifer plantations in the boreal forests of Canada. We present vegetation management alternatives screened based on their treatment efficacy, which we defined as their ability to (a) control competitive vegetation and (b) not cause undue damage to conifer seedlings. The treatments reviewed range from pre-harvest (preventative) to post-plant release (reactive) treatments, and are organized into five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…These are: preventive silviculture and natural regeneration, mechanical site preparation, early planting of size-adapted stock, and use of mechanical release where and when needed (Thiffault and Roy 2010). The common alternative to herbicides is cutting either by motor-manual or mechanical means (Wiensczyk et al 2011). We found that applying a cutting treatment once, although not as profitable as aerial application of herbicides, is economically viable.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These are: preventive silviculture and natural regeneration, mechanical site preparation, early planting of size-adapted stock, and use of mechanical release where and when needed (Thiffault and Roy 2010). The common alternative to herbicides is cutting either by motor-manual or mechanical means (Wiensczyk et al 2011). We found that applying a cutting treatment once, although not as profitable as aerial application of herbicides, is economically viable.…”
Section: Discussionmentioning
confidence: 83%
“…Although herbicides are cost-effective, their use in forest management continues to be contentious affecting operations in the forestry sector (Wyatt et al 2011, this issue). At the same time, the need for forest vegetation management to favour certain species and increase the productivity of Crown forests is also recognized (see Wiensczyk et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, with greater fire severity most of the organic matter is consumed and mineral soil is heated, causing local extinction or minimal regeneration [43,44]. On recently disturbed soils, rhizomes of ericaceous shrubs are stimulated by light and high soil temperatures [45], favouring extensive recovery following fire if the ericaceous species were abundant before the fire. Among ericaceous shrubs, rhizomes of Vaccinium angustifolium L. are the most resistant to heat [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, landscape-level implications and the indirect effects of herbicide reduction on forest management objectives related to wildlife habitat supply, quantity of old growth, wood supply, and forest management infrastructure (such as road networks) are less well known. While vegetation management alternatives may result in similar composition (Dampier et al 2006), growth rates (Bell et al 2011a), and wildlife habitat at the stand level (Lautenschlager et al 1997, Fortier et al 2005, Swift and Bell 2011, even subtle differences could equate to significant landscape-level changes when applied to millions of hectares over long periods.…”
Section: Introductionmentioning
confidence: 99%
“…While minimizing competition and providing crop trees with increased access to site resources (Balandier et al 2006, Wiensczyk et al 2011, it is also the primary tool for achieving management objectives related to forest composition and structure. In much of Canada's boreal forest, herbicide, motor-manual, and mechanical treatments are the most commonly used vegetation management options (Thompson and Pitt 2003, Fortier and Messier 2006, CCFM 2008.…”
Section: Introductionmentioning
confidence: 99%